The beneficial effect of Hangesha-shin-to (TJ-014) in gentamicin-induced hair cell loss in the rat cochlea. Issue 5 (October 2016) - Niwa, Katsuki; Matsunobu, Takeshi; Kurioka, Takaomi; Kamide, Daisuke; Tamura, Atsushi; Tadokoro, Shin; Satoh, Yasushi; Shiotani, Akihiro
Abstract: Objective: Ototoxic damage caused by aminoglycosides (AG) leads to the loss of cochlear hair cells (HCs). In mammals, mature cochlear HCs are unable to regenerate, and their loss results in permanent hearing deficits. Our objective was to protect the inner ear from damage after an AG challenge. The generation of reactive oxygen species (ROS), one of the earliest events in the process of AG ototoxicity, is considered to play a key role in the initiation of HC death. We examined whether Hangesha-shin-to (TJ-014), a traditional Japanese Kampo medicine considered to be a potent antioxidant, protects HCs from gentamicin (GM)-induced damage. Methods: Organ of Corti explants removed from postnatal day 3–5 rats were maintained in tissue culture and exposed to 50 μM GM for up to 48 h. The effects of TJ-014 on GM-induced ototoxicity were assessed by HC counts and immunohistochemistry against cleaved caspase-3, 8-hydroxy-2′-deoxyguanosine (8-OHdG), and a probe reacting to mitochondrial function changes. Results: TJ-014 treatments significantly reduced GM-induced HC loss and immunoreactivities for cleaved caspase-3 and 8-OHdG; these effects were correlated with increasing TJ-014 concentrations. Moreover, TJ-014 protected the mitochondrial membrane potential from GM ototoxicity. Conclusion: These findings indicate the potential of TJ-014 to prevent GM-induced cochlear damage involving ROS.